2007
DOI: 10.1243/14644207jmda106
|View full text |Cite
|
Sign up to set email alerts
|

The effect of weld metal anisotropy on the creep of a pressurized, circumferentially welded pipe

Abstract: A finite element implementation of the Hill anisotropic model has been applied to the problem of the determination of the steady-state creep behaviour of an internally-pressurised, two-material, axisymmetric P91 welded pipe. The anisotropic model results have been validated against an available analytical solution using homogeneous steady-state creep properties. In the two-material model, the parent (base) metal is assumed to be isotropic while the weld metal is assigned different creep properties in the weldi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2008
2008

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…equation ( 10) and the associated scalar rupture terms in equation ( 11), and on the other hand to possible assumptions about the relative propensities of void or cavitation damage growth under tension-dominated and compression-dominated loading. The present material model is developed primarily for application to pressurized welded connections, which are typically tensile hoop and tensile axial stress dominated; see reference [8], for example, for a detailed parametric analysis of the stress distributions in a circumferentially welded pipe using an anisotropic steady state creep material model based on equations (17) and (18). The particular choice of stress dependence of equations ( 11) is well established for isotropic damage-based life predictions for notched specimens and for pressurized piping applications (see, for example, reference [4]).…”
Section: Anisotropic Creep Damage Model For P91 Weld Metalmentioning
confidence: 99%
See 2 more Smart Citations
“…equation ( 10) and the associated scalar rupture terms in equation ( 11), and on the other hand to possible assumptions about the relative propensities of void or cavitation damage growth under tension-dominated and compression-dominated loading. The present material model is developed primarily for application to pressurized welded connections, which are typically tensile hoop and tensile axial stress dominated; see reference [8], for example, for a detailed parametric analysis of the stress distributions in a circumferentially welded pipe using an anisotropic steady state creep material model based on equations (17) and (18). The particular choice of stress dependence of equations ( 11) is well established for isotropic damage-based life predictions for notched specimens and for pressurized piping applications (see, for example, reference [4]).…”
Section: Anisotropic Creep Damage Model For P91 Weld Metalmentioning
confidence: 99%
“…Another objective of the work presented in this paper is to investigate the effects of weld material anisotropy on creep life predictions of realistic P91 pipe weldments using the developed anisotropic creep damage methodology. Previous work on the secondary creep behaviour of P91 welds under internal pressure and axial loads by Hyde et al [8] has shown that anisotropy has a significant effect on the steady state stresses under high end load conditions. Therefore, FE analyses of an axisymmetric pipe weld containing four material zones [10,11] i.e.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation